Severe cutaneous eruptions following the topical use of preparations containing bufexamac: Is it time to reconsider its registration in Australia?. (28th August 2018) - Harris, Adam G; Saikal, Samra L; Scurry, Jim; Relic, John; Nixon, Rosemary L; Chee, Paul
Abstract: Despite being a well‐recognised cause of allergic contact dermatitis with an embargo in many countries around the world, bufexamac is available over the counter in topical preparations in Australia. We present a series of patients who developed severe cutaneous eruptions after the topical application of bufexamac containing preparations to highlight the potential risks of this medication, as well as advocate for the reconsideration of its registration by the Therapeutic Goods Administration in Australia.